2016
DOI: 10.1007/s11064-016-1886-0
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta Peptides Affect Pregnenolone and Pregnenolone Sulfate Levels in PC-12 and SH-SY5Y Cells Depending on Cholesterol

Abstract: Increased amyloid beta (AB) peptide concentration is one of the initiating factors in the neurodegeneration process. It has been suggested that cholesterol induces the synthesis of AB peptide from amyloid precursor protein or facilitates the formation of amyloid plaque by lowering the aggregation threshold of the peptide. It is also shown that AB peptides may affect cholesterol metabolism and the synthesis of steroid hormones such as progesterone and estradiol. Pregnenolone (P) and pregnenolone sulfate (PS) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Studies in premenopausal women administered with the progesterone-only pill have shown marginal reductions in the levels of circulating total cholesterol and triglycerides [45]. However, it has been suggested that the administration of progesterone derivatives is able to blunt the changes in serum lipid profiles due to estrogen [46].…”
Section: Contribution Of Hormones To the Metabolic Adaptations Duringmentioning
confidence: 99%
“…Studies in premenopausal women administered with the progesterone-only pill have shown marginal reductions in the levels of circulating total cholesterol and triglycerides [45]. However, it has been suggested that the administration of progesterone derivatives is able to blunt the changes in serum lipid profiles due to estrogen [46].…”
Section: Contribution Of Hormones To the Metabolic Adaptations Duringmentioning
confidence: 99%
“…The results of the supplementary experiments showed that both Aβ 1-42 and Aβ 1-40 significantly induced decrease in cell viability, and there are no significant differences in cell viability between Aβ 1-40 and Aβ 1-42 treatment (Supporting Information Figure S1A), which is consistent with the previous study. [36] In addition, EGCG treatment also significantly inhibited the expression levels of GRP78, CHOP and cleaved-caspase12 in both Aβ 1-42 -and Aβ 1-40 -induced Figure 5. Effect of EGCG on cleaved-caspase3 expression in the cerebral cortex of APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 91%
“…As Aβ 1‐40 and Aβ 1‐42 are two of the most common neurotoxic fragments of Aβ peptides and have been widely used in the study of AD, we checked the effects of Aβ 1‐40 as a comparative control in our study. The results of the supplementary experiments showed that both Aβ 1‐42 and Aβ 1‐40 significantly induced decrease in cell viability, and there are no significant differences in cell viability between Aβ 1‐40 and Aβ 1‐42 treatment (Supporting Information Figure S1A), which is consistent with the previous study . In addition, EGCG treatment also significantly inhibited the expression levels of GRP78, CHOP and cleaved‐caspase12 in both Aβ 1‐42 ‐ and Aβ 1‐40 ‐induced SH‐SY5Y cells (Supporting Information Figure S1B–E), suggesting that EGCG protected against both Aβ 1‐42 ‐ and Aβ 1‐40 ‐induced neurotoxicity by attenuating ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…These reduced PREGS and DHEAS levels suggested that the 3β-HST enzyme involved in their biosynthesis was reduced. However, Calan et al 2016 [ 40 ] showed that toxic doses of Aβ significantly increased PREGS cellular levels in a time-dependent manner in SH-SY5Y cultured cells as compared to control cells ( Figure 2 A). This enhanced steroid production was interpreted as a result of self-defense probably to overcome harmful effects of Aβ.…”
Section: Dysregulated Brain Steroidogenesis and Steroid Concentratmentioning
confidence: 96%
“…In the studies by Marx et al 2006 and Naylor et al 2010 [ 41 , 42 ], high DHEA and PREG concentrations were observed in the prefrontal and temporal cortices of AD patients and tended to be positively correlated with Braak and Braak stage [ 41 ]. Similarly, in SH-SY5Y neuronal cells, treatment with Aβ peptides (Aβ 25–35 , Aβ 1–40 or Aβ 1–42 ) at toxic doses significantly enhanced PREG levels [ 40 ] ( Figure 2 B). PREG levels were higher in the group treated with Aβ 25–35 than the two others and proportionate to cell cholesterol content.…”
Section: Dysregulated Brain Steroidogenesis and Steroid Concentratmentioning
confidence: 99%